REVIEW: INOVASI TEKNOLOGI FARMASI DALAM MENINGKATKAN KEPATUHAN PENGOBATAN PADA PASIEN PEDIATRIK DAN GERIATRIK - Deisberanda, Fortunata Saesarria; Rommy, Rommy (Journal Pharmacy Of Tanjungpura, 2025)
This article reviews innovations in pharmaceutical technologies aimed at improving medication adherence in pediatric and geriatric patients, with a focus on innovative formulations. The purpose of this review was to assess the effectiveness of novel formulations in enhancing therapeutic outcomes and patient adherence, as well as to identify challenges in their clinical implementation. The findings from various studies indicate that technologies such as 3D printing, orally disintegrating tablets (ODTs), and chewable tablets improve therapeutic results and patient compliance by offering flexibility in dose adjustments and drug delivery. Additionally, formulations tailored to patient preferences, such as gummies and orally disintegrating films, have proven effective in enhancing medication acceptance, especially in pediatric and geriatric populations. While these technologies show great potential, challenges related to regulation and manufacturing barriers, such as quality standardization and production scalability, remain major obstacles. Therefore, further and more comprehensive research is required to ensure the widespread implementation of these technologies in pediatric and geriatric patient care.